Mechanical Behavior Analysis of High Strength Concrete Beams in Architectural Design: Simplified Calculation Method of Flexural and Shear Bearing Capacity - Peng, Yu; Zhou, Shuang (European Journal of Computational Mechanics, 2024)
This study advances the use of high-strength concrete beams in structural engineering by analyzing their flexural behavior. Utilizing a combination of theoretical and empirical methods, the research develops equations for calculating the cracking moment and ultimate load capacity of these beams. Key findings include a shear-bearing capacity calculation model, validated by experimental data, with discrepancies in cracking moment and ultimate load-bearing capacity formulas being only 6.16% and 1.53% respectively. These results offer significant insights for the design and analysis of high-strength concrete beams in architectural engineering, demonstrating high accuracy and stability.